A Google Classroom Based English Instruction at SMPN 1 Parepare - Kuba, Ruslan; Rahman, Ali Wira; Sianna, Sianna (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
In student perceptions, researchers found several things such as the ease of communicating, interacting, obtaining information, and flexibility in accessing learning materials. However, in this case students do not support the use of the Google Classroom application during learning because it is only for collecting assignments during online classes. In addition, the teacher's perception also has the same results as students. Researchers found several points of teacher perception such as the ease of presenting teaching materials, communication and information, and the ease of using gadgets. However, the teacher received complaints from students regarding the application of Google Classroom, such as a lack of understanding of the material being taught, the student's laziness factor, and constraints on quotas during learning and as for the distribution of special questionnaries for students, most students did not really like the application of Google Classroom in the learning process. shows that the learning media does not affect student learning motivation at SMP Negeri 1 Parepare, especially in class V.III.10 seen from the response of the teacher who said that there was a decrease in enthusiasm for learning when the use of the Google Classroom Application was added without the support and supervision of parents so that it makes students more lazy to take part in the teaching and learning process online. Therefore the use of Google Classroom does not affect students' learning motivation.The results of research on student and teacher perceptions of the application of Google Classroom show that learning is implemented using Google Classroom is not optimal and not optimal so it does not affect student learning motivation which raises several student perceptions of the application of learning media using Google Classroom media.